Overload on the presence of anxiety, depression and stress in caregivers of disabled people - Castelo-Rivas, Walter Patricio (2023)
Objective. To identify the relationship between overload and the presence of  stress, anxiety, and depression stress in caregivers of disabled people. Methods. The study was quantitative, correlational in scope and cross-sectional in design. A total of 384 caregivers of people with disabilities were part of the study sample, selected by convenience sampling. A survey with 47 questions was administered. Statistical analyses were developed in Statistical Package for Social Sciences 24, calculating both the normality of the data and the  correlations of the variables. Results. There was a relationship between  caregiver overload and the presence of stress, anxiety and depression in caregivers of people with disabilities, since the excess of activities generated as a result of caring for people with disabilities was strongly related to the presence of stress and moderately related to anxiety and depression. Conclusion. It was identifed that caregiver overload influences the presence of anxiety, depression and stress.